Low-Income Consumer Behavior: A Literature Review (2024)
Objective: The objective of this literature review is to present the theoretical bases to describe, analyze, and interpret the factors associated with the behavior of low-income consumers. Theoretical Framework: The literature review addresses the concepts of consumer behavior, the factors that influence this behavior, such as psychological, social and cultural factors, and finally the low-income consumer. Method: A non-experimental design of bibliographic research allowed us to systematically review the constructs of consumer behavior, factors associated with consumption behavior, and low-income consumers. A total of 109 bibliographic references were consulted: 71 articles, 31 books, 5 research-results book chapters, and 2 reports. Results and Discussion: The review found that this market segment is heterogeneous due to sociocultural differences in the contexts where they reside. For poverty to be more attractive to the business sector, it is necessary that the proposed solution be sustainable; therefore, it must be profitable. The participation of the State is also important, responsible for the inclusion of public policies that encourage companies to incorporate low-income people as micro-entrepreneurs in their business model; one proposal would be to establish dignified and flexible forms of contracting. It is recommended that business schools include within the content of their undergraduate and graduate programs consumer behavior focused on low-income people, who make up the majority of the market in developing countries, in order to raise awareness among future professionals of the importance of including this segment in marketing strategies. Research Implications: The theoretical content found in the literature review will serve marketing managers to design strategies in the distribution and marketing processes that enable products to be introduced into the low-income consumer segment, as well as encouraging the scientific community from the business field to investigate this market segment. Originality/Value: The bibliographic study contributes to the marketing literature with an innovative approach, by addressing the low-income consumer, an object of study that is often excluded in the business sector, considering that they do not have purchasing power, but that in emerging markets represents the majority. of the population.